Expression of lactate dehydrogenase C correlates with poor prognosis in renal cell carcinoma. Issue 3 (March 2017) - Hua, Yibo; Liang, Chao; Zhu, Jundong; Miao, Chenkui; Yu, Yajie; Xu, Aimin; Zhang, Jianzhong; Li, Pu; Li, Shuang; Bao, Meiling; Yang, Jie; Qin, Chao; et al.
Lactate dehydrogenase C is an isoenzyme of lactate dehydrogenase and a member of the cancer–testis antigens family. In this study, we aimed to investigate the expression and functional role of lactate dehydrogenase C and its basic mechanisms in renal cell carcinoma. First, a total of 133 cases of renal cell carcinoma samples were analysed in a tissue microarray, and Kaplan–Meier survival curve analyses were performed to investigate the correlation between lactate dehydrogenase C expression and renal cell carcinoma progression. Lactate dehydrogenase C protein levels and messenger RNA levels were significantly upregulated in renal cell carcinoma tissues, and the patients with positive lactate dehydrogenase C expression had a shorter progression-free survival, indicating the oncogenic role of lactate dehydrogenase C in renal cell carcinoma. In addition, further cytological experiments demonstrated that lactate dehydrogenase C could prompt renal cell carcinoma cells to produce lactate, and increase metastatic and invasive potential of renal cell carcinoma cells. Furthermore, lactate dehydrogenase C could induce the epithelial–mesenchymal transition process and matrix metalloproteinase-9 expression. In summary, these findings showed lactate dehydrogenase C was associated with poor prognosis in renal cell carcinoma and played a pivotal role in the migration and invasion of renal cell carcinoma cells. Lactate dehydrogenase C may act as a novel biomarker for renal cell carcinoma progression and a potential therapeutic target for the treatment of renal cell carcinoma.